Standard operating procedures: for BRAC's emergency response in Bangladesh - BRAC (Disaster, Environment and Climate Change Programme (DECCP), BRAC, 2016)
1. BRAC Programme Activities 2. Current Disaster Management System of BRAC 3. Risk Profile of Bangladesh 4. Existing early warning system 5. Communication flow 6. Incident Command System (ICS) 7. Standard Operating Procedures (SOP) 8. Monitoring and evaluation framework 9. Key challenge areas.